Bread and steel: Harcourt on the economic surplus, employment and distribution in two-sector economies - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2022)
The present paper is set out to examine the place of Geoff Harcourt's 1965 "Two-sector model of the distribution of income and the level of employment in the short run" in his research agenda, as well as its original historical context and fate. That pioneer model articulated how the production of the potential economic surplus in the consumption goods sector, and its realization as actual surplus through aggregate demand coming from investment in the capital goods sector decided, together with the mark-up in the consumption sector, the level of employment and the distribution of income. The connections between Harcourt's model and M. Kalecki's similar approach are also tackled in the paper, together with the reasons for the relative little impact of that model in the literature despite its initial success at a Cambridge seminar at the time.
Keywords: B22; E11; E12; 330; Harcourt; two-sector; economic surplus; mark-up; employment